DEVELOPMENT OF EMOTIONAL INTELLIGENCE IN MIDDLE SCHOOL STUDENTS THROUGH ISLAMIC EDUCATION - Mundofi, Ahmad Asron; Ulfa, Siti Marya; Fahrudi, Emi; Urokhim, Auliya; Al-Rawafi, Abdulkhaleq (Prodi Pendidikan Agama Islam STAI Darul Falah, 2024)
This study aims to understand the development of emotional intelligence in middle school students. The research method used is qualitative, employing a library research approach to gather information. Both primary and secondary data sources were used. Primary sources include books, journal articles, or national and international scientific publications. Secondary sources are derived from studies relevant to the research topic. For data analysis, the authors referred to Miles and Huberman's framework, which includes data collection, data reduction, and conclusion drawing. The results of this study highlight several aspects of emotional intelligence: recognizing one's own emotions, managing emotions, self-motivation, recognizing others' emotions (empathy), and building relationships. Emotional intelligence is crucial to be enhanced and developed in students at school, as middle school is a pivotal age for emotional development. One effective way to improve students' emotional intelligence is through the implementation of Islamic education, because students will become emotionally intelligent and their learning outcomes will improve.